Developing athletic motor skill competencies in youth - Radnor, J. M.; Moeskops, S.; Morris, S. J.; Mathews, T. A.; Kumar, N. T.; Pullen, B. J.; Meyers, R. W.; Pedley, J. S.; Gould, Z. I.; Oliver, J. L.; Lloyd, R. S. (Strength and Conditioning Journal, 2020)
Synergistic development of muscular strength and motor skill competency is central to long-term athletic development. However, these qualities need to be developed in a logical and progressive manner, and training methods need to be developmentally appropriate, engaging, and enjoyable for young athletes to help them build a positive association with strength and conditioning-based activities. This article aims to provide a resource for coaches to use when developing the athletic motor skill competencies in youth, including game-based activities, and a more structured resistance training curriculum.